Electrochemical behaviour of AA2198 and AA2139 in neutral solutions. Issue 8 (29th January 2015) - Balbo, A.; Frignani, A.; Grassi, V.; Zucchi, F.
<x xml:space="preserve">Abstract</x> The corrosion behaviour of innovative Li‐containing (AA2198) and Ag‐containing (AA2139) aluminium alloys was investigated by means of electrochemical techniques in neutral media (sulphate and chloride solutions). Li presence caused a more active corrosion potential in the initial immersion times, but successively, the corrosion potentials of AA2198 became about 100 mV more positive than those of AA2139. Although in chloride media these alloys presented the same cathodic polarization curves, the passivity interval of AA2198 was characterized by lower passive currents and more positive pitting potentials than AA2139. Such differences were attributed to different amounts of intermetallic dispersoids between these aluminium alloys